Evaluating alternative policy responses to higher world food prices: The case of increasing rice prices in Madagascar - Coady, David; Dorosh, Paul A.; Minten, Bart (Wiley, 2009)
Higher world food prices have led many developing countries to adopt policies to mitigate the impact on low‐income households. This article sets out a partial equilibrium framework to evaluate the efficiency, distributional, and revenue implications of alternative policy responses. The model is applied to evaluate tariff reductions and targeted transfers in Madagascar. Although lowering tariffs generates substantial efficiency gains, these accrue mainly to the top half of the welfare distribution, and poor net sellers are actually worse off. Developing a system of targeted direct transfers to poor households is likely to be a substantially more cost‐effective approach to poverty alleviation.